2022
DOI: 10.1038/s41598-022-05060-x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive asprosin detection in clinical samples reveals serum/saliva correlation and indicates cartilage as source for serum asprosin

Abstract: The C-terminal pro-fibrillin-1 propeptide asprosin is described as white adipose tissue derived hormone that stimulates rapid hepatic glucose release and activates hunger-promoting hypothalamic neurons. Numerous studies proposed correlations of asprosin levels with clinical parameters. However, the enormous variability of reported serum and plasma asprosin levels illustrates the need for sensitive and reliable detection methods in clinical samples. Here we report on newly developed biochemical methods for aspr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…When recombinant asprosin was subjected to size exclusion chromatography (SEC), the obtained chromatogram showed two main asprosin containing peaks eluting at fraction numbers corresponding to higher molecular weight species (Fig. 3A) than the previously determined 37 kDa of glycosylated recombinant asprosin (14). In line with this finding, analysis of asprosin fractions directly after affinity purification by native-PAGE revealed the accumulation of asprosin in the stacking gel with no detected migration into the gel (Fig.…”
Section: Intrinsic Multimerization Ability Of Recombinant Asprosinsupporting
confidence: 79%
See 1 more Smart Citation
“…When recombinant asprosin was subjected to size exclusion chromatography (SEC), the obtained chromatogram showed two main asprosin containing peaks eluting at fraction numbers corresponding to higher molecular weight species (Fig. 3A) than the previously determined 37 kDa of glycosylated recombinant asprosin (14). In line with this finding, analysis of asprosin fractions directly after affinity purification by native-PAGE revealed the accumulation of asprosin in the stacking gel with no detected migration into the gel (Fig.…”
Section: Intrinsic Multimerization Ability Of Recombinant Asprosinsupporting
confidence: 79%
“…In the current view, asprosin is mainly produced by WAT from where it is released into the blood in monomeric form. However, our previous findings showed that asprosin is synthesized and secreted by connective tissue resident cells such as fibroblasts and chondrocytes (14) -a finding which supports the notion of local asprosin storage within tissue-specific microenvironments. Here, by employing newly generated specific asprosin antibodies we monitored the distribution pattern of asprosin in various human and murine connective tissues, including placenta, and muscle.…”
Section: Introductionsupporting
confidence: 65%
“…The asprosin sandwich ELISA was produced in our laboratory, intensively tested and validated by surface plasmone resonance and interaction studies ( 16 ). The detection sensitivity ranged at <65 pg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been recently shown that asprosin is expressed in human placenta and elevated in the plasma of pregnant women complicated with GDM and their fetal umbilical blood ( 14 ). Since there is an urgent need for a reliable and sensitive method to determine plasma asprosin levels ( 15 ), our laboratory took the initiative to develop a functional and dependable asprosin ELISA ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported measurable amounts of asprosin in different body fluids such as saliva, breast milk, urine, serum, and plasma ( 18 20 ). Interestingly, asprosin was found to be expressed in the ovaries, placenta and human cartilage ( 19 , 21 , 22 ). A strong correlation was reported between serum asprosin levels and a specific marker for cartilage degradation termed cartilage oligomeric matrix protein (COMP) in patients subjected to total hip replacement surgery ( 19 ).…”
Section: Asprosin Secretion and Expressionmentioning
confidence: 99%